The genus kirchneriella schm. (chlorophyceae) in argentina: Taxonomy and geographic distribution - Couté, Alain (2011)
This note deals with the taxonomic study and geographic distribution of the genus Kirchneriella Schm. in Argentina, where species and infraspecific taxa have received little attention. The classification of taxa is based on morphological and morphometric characters. Thirteen species and three varieties are recorded, among them K. contorta var. elegans (Playf.) Kom., K. danubiana Hind., K. irregularis var. spiralis Kors. and K. obtusa (Kors.) Kom. are new records for Argentina.